Stimulation of Naïve Monocytes and PBMCs with Coagulation Proteases Results in Thrombin‐Mediated and PAR‐1‐Dependent Cytokine Release and Cell Proliferation in PBMCs Only. (23rd April 2013) - Nieuwenhuizen, L.; Falkenburg, W. J. J.; Schutgens, R. E. G.; Roosendaal, G.; van, K.; Biesma, D. H.; Lafeber, F. P. J. G.
Abstract Protease‐activated receptors (PARs) are stimulated by proteolytic cleavage of their extracellular domain. Coagulation proteases, such as FVIIa, the binary TF‐FVIIa complex, free FXa, the ternary TF‐FVIIa‐FXa complex and thrombin, are able to stimulate PARs. Whereas the role of PARs on platelets is well known, their function in naïve monocytes and peripheral blood mononuclear cells (PBMCs) is largely unknown. This is of interest because PAR‐mediated interactions of coagulation proteases with monocytes and PBMCs in diseases with an increased activation of coagulation may promote inflammation. To evaluate PAR‐mediated inflammatory reactions in naïve monocytes and PBMCs stimulated with coagulation proteases. For this, PAR expression at protein and RNA level on naïve monocytes and PBMCs was evaluated with flow cytometry and RT‐PCR. In addition, cytokine release (IL‐1β, IL‐6, IL‐8, IL‐10, TNF‐α) in stimulated naïve and PBMC cell cultures was determined. In this study, it is demonstrated that naïve monocytes express all four PARs at the mRNA level, and PAR‐1, ‐3 and ‐4 at the protein level. Stimulation of naïve monocytes with coagulation proteases did not result in alterations in PAR expression or in the induction of inflammation involved cytokines like interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), interleukin‐8, interleukin‐10 or tumour necrosis factor‐α. In contrast, stimulation of PBMCs with coagulation proteases resulted in thrombin‐mediated induction of IL‐1β and IL‐6 cytokine production and PBMC cell proliferation in a PAR‐1‐dependent manner. These data demonstrate that naïve monocytes are not triggered by coagulation proteases, whereas thrombin is able to elicit pro‐inflammatory events in a PAR‐1‐dependent manner in PBMCs.